Inovasi Produk Baru Dengan Sukuk Musyarakah Wal Ijarah Sebagai Solusi Pengembangan Infrastuktur Di Indonesia - Azinuddin Syaiful Haq; Siti Murtiyani (At-Tauzi : Jurnal Ekonomi Islam, 2010)
Infrastructure development is the basic capital of economic development in Indonesia. The weakening of infrastructure development is one of the factors that has caused Indonesia to lag behind other countries in driving economic development over the past thirty years. The availability of infrastructure is fundamental to sustainable economic development. To increase infrastructure development, the government will be supported by funding of $ 1,400 billion. The plan will be fulfilled from various funding sources, such as Aceh assistance (1 percent), the national development budget (17 percent), and domestic (21 percent). From this scheme, there is a funding gap of IDR 810 billion, which there is no certainty that the government will cover it. This condition shows the need for a breakthrough by the government to cover the funding gap. This innovation is needed for sharia-based funding and opportunities to get funding from outside parties, especially investors who want a sharia concept that generates profits from returns. With the concept of Sukuk Musharakah wal Ijarah, it is hoped that it can be the right solution for funding infrastructure development in Indonesia.